1983
DOI: 10.1159/000249790
|View full text |Cite
|
Sign up to set email alerts
|

The Histology of Eccrine Poromas: A Study of 14 Cases

Abstract: A histological study of 14 eccrine poromas in 14 different patients was conducted and the results correlated with the clinical data. Histologically, an eccrine poroma is an easily recognizable epithelial skin tumor. Three morphological variants can be identified: a benign, a premalignant or dysplastic, and an invasive, malignant form. These tumors hardly have a typical clinical appearance. Symptoms such as bleeding, pain and itching are suggestive of a possible malignant transformation. There seems to be a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
2
3

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 11 publications
1
44
2
3
Order By: Relevance
“…And benign poroma form less than 10% of these making it a highly uncommon diagnosis. 8 It is generally found on acral locations, but can be found on almost any cutaneous surface.…”
Section: Discussionmentioning
confidence: 99%
“…And benign poroma form less than 10% of these making it a highly uncommon diagnosis. 8 It is generally found on acral locations, but can be found on almost any cutaneous surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, eccrine poroma has been rarely reported on the forearm. The pathogenesis is unknown, but actinic damage, radiation, trauma and the human papilloma virus have been implicated [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Although eccrine poroma is known to be benign, the variants of eccrine poroma seem to frequently have malignant features. Pylyser et al 7 reported that almost 50% of eccrine poromas exhibited malignant biological behaviors, and Robson et al 9 reported that coexistence between benign eccrine poroma and eccrine porocarcinoma is encountered in up to 11% of the cases. Importantly, the bleeding tendency without pain or itching has not been recognized as the hall marker of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depuis la première description de Smith et Coburn [15] en 1956 sous l'appellation d'hidroacanthome malin, de rares cas de po rocarcinome ont été rapportés isolément [1][2][3][4][5]7,8,[10][11][12][13]15,16]. Récemment, la lit térature s'est enrichie d'une série de 27 cas rapportés par Schaw et al [14] et de 18 cas par Mehregan et al [9].…”
Section: Discussionunclassified